SOME ASPECTS OF INCREASING THE EFFECTIVENESS OF PHARMACOTHERAPY FOR ACUTE PNEUMONIA IN YOUNG CHILDREN (World Bulletin of Public Health, 2023)
Endogenous intoxication syndrome (EIS) continues to be one of the most pressing problems in pediatrics to this day. About 90% of all pathological conditions in pediatrics occur against the background of endogenous intoxication
Keywords: Endogenous intoxication; pneumonia in children; effectiveness of drugs